Multiple Sclerosis and the Endogenous Opioid System - Dworsky-Fried, Zoë; Chadwick, Caylin I.; Kerr, Bradley J.; Taylor, Anna M. W. (Frontiers in Neuroscience, 2021)
Multiple sclerosis (MS) is an autoimmune disease characterized by chronic inflammation, neuronal degeneration, and demyelinating lesions within the central nervous system. The mechanisms that underlie the pathogenesis and progression of MS are not fully known and current therapies have limited efficacy. Preclinical investigations using the murine experimental autoimmune encephalomyelitis (EAE) model of MS, as well as clinical observations in patients with MS, provide converging lines of evidence implicating the endogenous opioid system in the pathogenesis of MS. In recent years, it has become increasingly clear that endogenous opioid peptides, binding μ- (MOR), 𝜅- (KOR) and 𝛿-opioid receptors (DOR), function as immunomodulatory molecules within both the immune and nervous systems. The endogenous opioid system is also well known to play a role in the development of chronic pain and negative affect, both of which are common comorbidities in MS. As such, dysregulation of the opioid system may be a mechanism that contributes to the pathogenesis of MS and associated symptoms. Here, we review the evidence for a connection between the endogenous opioid system and MS. We further explore the mechanisms by which opioidergic signaling might contribute to the pathophysiology and symptomatology of MS.